2009
DOI: 10.1007/s00244-009-9414-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Veterinary Pharmaceutical Ivermectin on Soil Invertebrates in Laboratory Tests

Abstract: As part of the risk assessment of veterinary pharmaceuticals, the potential impact of these chemicals on soil ecosystems has to be determined according to European law. However, almost no data from standardized laboratory tests are available. Therefore, in the EU FP6 ERAPharm, the effects of the widely used veterinary pharmaceutical ivermectin, an anthelminthic, were studied in chronic laboratory tests performed according to OECD (Organisation for Economic Co-operation and Development) and ISO (International O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 18 publications
4
26
0
1
Order By: Relevance
“…In fact, for reasons not clear yet the reaction of earthworms and enchytraeids was positive. The high sensitivity of collembolans is well in line with test data gained in the laboratory (Jensen et al 2003;Römbke et al 2010). On the community level, a significant impact was detected at all sampling dates.…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…In fact, for reasons not clear yet the reaction of earthworms and enchytraeids was positive. The high sensitivity of collembolans is well in line with test data gained in the laboratory (Jensen et al 2003;Römbke et al 2010). On the community level, a significant impact was detected at all sampling dates.…”
Section: Methodssupporting
confidence: 74%
“…Data from literature confirm the low to moderate sensitivity of enchytraeids and earthworms to ivermectin, indicating effects on reproduction for both groups in the low mg/kg range (e.g. NOECs: 3.0 and 2.5 mg ivermectin/kg soil dw, respectively) (Jensen et al 2003;Römbke et al 2010).…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…[4] A 2002 review of pharmaceutical contaminants in the environment reports that the overall excretion rates of unmetabolized chlortetracycline, oxytetracycline, and ivermectin in feces and urine in veterinary treatment are 17-75%, 20%, and 40-75%, respectively. [1] Numerous studies have been conducted on the environmental fate of avermectins with a focus on effects on dung arthropods, [5] soil invertebrates, [6][7] and aquatic ecosystems. [8] Studies looking at the mobility [9] and dissipation [10] of ivermectin in different soil types have shown that pH and cation exchange capacity of the soil can affect the ionic binding potential of ivermectin, and that the dissipation of ivermectin is slow in many soils under aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Embora as pesquisas conduzidas por Kaneda et al (2006) apontem que as concentrações ambientalmente relevantes de ivermectina não afetam as minhocas, outros estudos demonstraram que este endectocida prejudica os aspectos reprodutivos, como a produção e a eclodibilidade dos casulos (Gunn & Sadd 1994;Rombke et al, 2009) enquanto que a mortalidade só é evidenciada em concentrações elevadas, entre 56 mg kg -1 (Wang et al, 2012) e 314 mg kg -1 (Halley et al, 1989). Recentemente, tem-se observado uma reemergência de estudos científicos em relação a um fenômeno conhecido como efeito hormético (Calabrese, 2005).…”
Section: Introductionunclassified